1999
DOI: 10.1159/000018070
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Sclerosis Revealing T-Cell Lymphoma

Abstract: We describe a case of systemic sclerosis (SSc) occurring together with malignant lymphoma. A 43-year-old man, who had noticed sclerodactyly 1 month before consultation, was admitted for progressive skin sclerosis on his forearms and chest. SSc was diagnosed. Immediately after admission, skin sclerosis rapidly extended to the neck and trunk, and subcutaneous tumors developed on the neck, chest and back. Skin sclerosis was prominent at the sites where subcutaneous tumors were present. The tumors were diagnosed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 14 publications
2
14
0
2
Order By: Relevance
“…There are reports of paraneoplastic scleroderma developing in association with T-cell lymphoma,1 gastric carcinoma,2 malignant melanoma as well as several other primary sites that have been described in the literature 3 4…”
Section: Discussionmentioning
confidence: 99%
“…There are reports of paraneoplastic scleroderma developing in association with T-cell lymphoma,1 gastric carcinoma,2 malignant melanoma as well as several other primary sites that have been described in the literature 3 4…”
Section: Discussionmentioning
confidence: 99%
“…Bien que rares, des observations troublantes de corré lation é volutive é troite entre sclé rodermie systé mique et lymphome font suspecter la ré alité du syndrome parané oplasique [8]. En effet, la sclé rose cutané e progresse rapidement lors du dé veloppement du lymphome, et elle ré gresse aprè s la ré mission de la lymphopathie sous l'effet de la chimiothé rapie [5,9,17,22,24]. Il est cependant impossible d'é carter la responsabilité directe de la chimiothé rapie sur la sclé rodermie systé mique, en particulier le cyclophosphamide et les sté roïdes qui peuvent amé liorer certaines atteintes viscé rales de cette connectivite [8].…”
Section: Discussionunclassified
“…Certains cas font discuter des syndromes cutané s sclé rodermiformes parané oplasiques plus que de ré elles associations sclé rodermie systé mique-lymphome [7,27]. Comme dans notre observation, la lymphopathie survient le plus souvent aprè s le diagnostic de sclé rodermie systé mique avec un dé lai moyen de six, huit ans (extrê mes : un à quatorze ans) [1,3,5,13,17,19,21,22,24,25,[28][29].…”
Section: Discussionunclassified
“…However, T cell lymphomas associated with PSS are quite rare. Hasegawa et al [7] reported a case of subcutaneous panniculitis-like T cell lymphoma associated with PSS. Our case is the first case report of AILT associated with PSS.…”
Section: Discussionmentioning
confidence: 99%